PENGARUH FLUKTUASI NILAI TUKAR RUPIAH DAN NILAI EKSPOR TERHADAP PPN DAN PPNBM DI INDONESIA PERIODE 2015-2024 - Novia Nurhalizah; Dita Anggraini; Nailah Arraswita (Universitas Logistik dan Bisnis Internasional, 2026)
This indicates that changes in the rupiah exchange rate and increased export values can contribute to the growth of tax revenue, although the impact is not always immediately apparent on an individual basis. The conclusion of this study confirms that exchange rate stability and export growth simultaneously play an important role in strengthening VAT revenue in Indonesia. This finding is expected to be considered by the government in formulating fiscal policies that are adaptable to global and domestic economic dynamics. The research results indicate that, partially, fluctuations in the rupiah exchange rate and export value have a positive but not significant impact on VAT revenue in Indonesia. The research method used is a quantitative approach with multiple linear regression analysis. However, simultaneously, both variables have a positive and significant impact on VAT revenue. The sampling technique used is saturation sampling, where the entire population (n = 10) is used as the research sample. This study aims to analyze the influence of fluctuations in the rupiah exchange rate and export value on Value Added Tax (VAT) revenue in Indonesia over the past decade. The research population regarding the rupiah exchange rate, export value, and VAT revenue was obtained from the Central Bureau of Statistics (BPS) and the Ministry of Trade (Kemendag) using data from a 10-year period. Time series data from 2015–2024 were analyzed using multiple linear regression with SPSS 25.